2009
DOI: 10.1002/job.615
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational democracy on employees' socio‐moral climate and prosocial behavioral orientations

Abstract: SummaryThis study investigates the effects of workers' perceived participation in democratic decision-making on their prosocial behavioral orientations, democratic values, commitment to the firm, and perceptions of socio-moral climate. The sample consists of 325 Germanspeaking employees from 22 companies in Austria, North Italy, and Southern Germany that vary in their level of organizational democracy (social partnership enterprises, workers' cooperatives, democratic reform enterprises, and employee-owned self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 45 publications
3
126
0
6
Order By: Relevance
“…The belief that their input is valued increases employees' trust in the firm's leadership (McCauley & Kuhnert, 1992), augments organizational commitment (Weber, Unterrainer, & Schmid, 2009) and enhances employee performance (Ye, Marinova, & Singh, 2007). Nutt (1998) examined 376 cases involving attempts to implement strategic decisions (including mergers, buyouts and restructuring), concluding that giving the parties a voice in the decision-making process greatly improved the chances of success.…”
Section: The International Journal Of Human Resource Management 15mentioning
confidence: 99%
“…The belief that their input is valued increases employees' trust in the firm's leadership (McCauley & Kuhnert, 1992), augments organizational commitment (Weber, Unterrainer, & Schmid, 2009) and enhances employee performance (Ye, Marinova, & Singh, 2007). Nutt (1998) examined 376 cases involving attempts to implement strategic decisions (including mergers, buyouts and restructuring), concluding that giving the parties a voice in the decision-making process greatly improved the chances of success.…”
Section: The International Journal Of Human Resource Management 15mentioning
confidence: 99%
“…Conversely, organizational democracy, which may extend to employee-owned and self-governed enterprises, may be the most comprehensive form of DLA (Wegge et al 2010). Studies have shown that democratic company structures are positively related with employee ethical value orientation and democratic engagement orientation towards society (Unterrainer et al 2011;Weber et al 2009). In addition to the potential positive effects of a democratic approach of DLA, there are concerns that distributed leadership is merely a new way to deliver top-down policies (Harris 2013).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…a climate of democratic participation in terms of cooperation, communication, openness, appreciation, trust and respect. The socio-moral climate describes context conditions for individual and organizational change, and innovation and is expected to be crucial for participative team processes (Weber et al, 2009). Regarding the team process, we focus on the processes of debating and integrating different viewpoints into decisions, as these processes are the most important steps in innovation processes (Scholl, 2009;Simons et al, 1999).…”
Section: Introductionmentioning
confidence: 99%